IMPLEMENTASI PENEGAKAN HUKUM LAUT TERHADAP PENCEMARAN SAMPAH DI PESISIR PANTAI PANJANG KOTA BENGKULU - rizqi, Tasya Bitha Zhafirah; Sania Afara Nadhifa; Tarisya Putri Ufairah; Ema Septiana; Arimbi Fajari Furqon (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Law enforcement on marine pollution, particularly waste pollution in coastal areas, is a strategic issue in maintaining environmental sustainability and marine ecosystems. This study aims to analyze the implementation of maritime law enforcement against waste pollution in the coastal area of Pantai Panjang, Bengkulu City. The research employs a qualitative approach with a descriptive method, using data collection techniques such as observation, interviews, and documentation studies.The results show that the implementation of law enforcement against waste pollution in the area has not been optimal. This is due to low public awareness, weak supervision, and limited coordination among related institutions. Although regulations are already in place, their implementation still faces various challenges, including limited resources and weak enforcement of sanctions.This study concludes that strengthening inter-agency coordination, increasing public awareness, and enforcing stricter and more consistent legal measures are necessary. The findings are expected to contribute to the development of more effective policies and strategies for managing waste pollution in coastal areas